Decarbonization in the European Steel Industry: Strategies, Risks, and Commitments - Giacomo Di Foggia; Massimo Beccarello (Environmental Challenges, 2024)
This paper investigates the challenge of decarbonizing the steel industry, a pillar of the global economy but also a major carbon emitter. Analyzing current decarbonization strategies, their effectiveness, and the role of corporate commitment and risk management offers insights needed to identify development paths in the current environment characterized by pressure driven by stringent environmental standards and fierce competition. An empirical approach, including a survey model and simulation, is used to answer prominent research questions. Aspects such as the influence of environmental and governance criteria, specific initiatives that can be undertaken, the importance of corporate commitment, and the integration of risk management into strategic planning are examined. Simulations suggest that the probability of meeting the 2030 goals range from 65.08 to 75.98 percent and the delta between low and high commitment ranges from 4.917 to 4.133 percent according to the share of renewables in the energy mix decarbonization. The influence of the energy mix is also included in the analysis. The research highlights the need for greater coordination and commitment across the industry to improve decarbonization efforts. It emphasizes the critical role of government policies and market dynamics in shaping industry actions toward achieving decarbonization goals. The findings contribute to understanding decarbonization processes, offering insights and guidance for the steel sector's transition to a low-carbon economy
Keywords: L6; Q5; 330; decarbonization; net-zero; ESG; SDG